2022
DOI: 10.17221/130/2021-pps
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic and induced resistance phenomena in cucumbers against the root-knot nematode (Meloidogyne incognita)

Abstract: Meloidogyne spp. is an important pest of cucurbits in tunnel farming of vegetables in Pakistan. A cucumber germplasm was evaluated for resistance against the root-knot nematode (RKN, Meloidogyne incognita) based on the number of galls and egg masses recorded under glass house conditions. All the cucumber accessions showed varying responses towards the RKN inoculation. Out of the fifteen cucumber lines, two were found to be moderately susceptible to M. incognita, ten were susceptible while the other three were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The defensive proteins that called pathogenesis-related proteins expressed by these genes in resistance or tolerance plant. Chemical induction of "systemic acquired resistance" is detected by using Benzothiadiazole in tomato and grapevines plants to suppress infection of M. incognita [79] and by using hydroxyurea in tomato to inhibit progress infection of M. javanica [80]. Also, chitosan stimulated production of defense-related chemicals in tomato plant and was associated through improvement process of resistance to root-knot nematode as well [81].…”
Section: Innovative Methodsmentioning
confidence: 99%
“…The defensive proteins that called pathogenesis-related proteins expressed by these genes in resistance or tolerance plant. Chemical induction of "systemic acquired resistance" is detected by using Benzothiadiazole in tomato and grapevines plants to suppress infection of M. incognita [79] and by using hydroxyurea in tomato to inhibit progress infection of M. javanica [80]. Also, chitosan stimulated production of defense-related chemicals in tomato plant and was associated through improvement process of resistance to root-knot nematode as well [81].…”
Section: Innovative Methodsmentioning
confidence: 99%
“…The four most predominant species are Meloidogyne incognita, Meloidogyne javanica, Meloidogyne arenaria, and Meloidogyne hapla. Moreover, research has identified over 3000 plant species, encompassing nearly all cultivated crops, as potential hosts for these nematodes [3].…”
Section: Introductionmentioning
confidence: 99%